2020
DOI: 10.3389/fspor.2020.597676
|View full text |Cite
|
Sign up to set email alerts
|

Body and Boat: Significance of Morphology on Elite Rowing Performance

Abstract: Objectives: The purpose of this study was to determine and weigh the anthropometric indicators that were associated with pacing performances for each Olympic rowing category.Methods: Between 2010 and 2015, 1,148 rowers (650 men and 498 women) participated in the finals of World Championships in each heavyweight Olympic event. They were categorized into four morphological clusters according to their height and body mass index (BMI): tall and thin (TT), tall and robust (TR), small and thin (ST), and small and ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In addition, traditional rowing courses are not held in parallel lanes, but between two and four lengths with one or three complete tacks, both in calm water and the sea. These technical and competitive differences between modalities, boats, and types of competition result in different functional and physiological demands [9], where anthropometric characteristics and body composition have a fundamental role in Olympic [10,11] and traditional [7,12] rowing performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, traditional rowing courses are not held in parallel lanes, but between two and four lengths with one or three complete tacks, both in calm water and the sea. These technical and competitive differences between modalities, boats, and types of competition result in different functional and physiological demands [9], where anthropometric characteristics and body composition have a fundamental role in Olympic [10,11] and traditional [7,12] rowing performance.…”
Section: Introductionmentioning
confidence: 99%
“…The differences between male and female rowers have also been analyzed, finding differences and similarities in anthropometric characteristics that could determine not only training programs but also offering indicators to be able to perform talent detection programs [18][19][20]. Even De Larochelambert [10] determined which morphologies (tall and thin, tall and robust, small and thin, or small and robust) had a significant effect on speed for both male and female rowers. On the other hand, the research also seem to determine that there are anthropometric characteristics that are related to the level of rowing performance such as height and length measurements [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, we must distinguish heavyweight and lightweight categories. According to the rules ( 9 ), a lightweight athlete competing in a single scull cannot exceed maximum weight limit of 72.5 kg for men, and of 59 kg for women. In all remaining crew disciplines (multiple athletes in a single boat), the average weight of the crew must not exceed 70 kg, and 57 kg respectively while at the same time no single male athlete can exceed 72.5 kg and 59 kg respectively for women.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Iglesias‐Soler et al (2021) observed that L 0 and v 0 were sensitive enough to identify changes on neuromuscular performance during the bench press and squat exercises following a five‐week resistance training programme with a traditional or cluster set configuration. However, since the physical and physiological characteristics of rowers are affected by the age category (Das, Mandal, Syamal, & Majumdar, 2019; De Larochelambert et al, 2020), of particular interest to coaches would be to know whether this novel testing methodology could be sensitive enough to differentiate neuromuscular performance between rowers of different age categories. Furthermore, to track changes in neuromuscular performance through a training cycle, it would also be of interest to identify which L‐V relationship variables are more related to rowing performance.…”
Section: Introductionmentioning
confidence: 99%